Application of the shari'ah in the Saudi courts : a study with special reference to commercial courts - Alaboudi, Ismail Mohammed (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2017)
The aim of the thesis is to examine Saudi Commercial Court's decisions from Shari'ah standpoint. The method of examining opinions in its context is not well known and discussed in the pre modern Islam. Therefore, researcher use some social sciences, Talal Asad's discursive tradition method is very helpful as a starting point. Meanwhile, Islamic jurisprudence, dialectic, and education utilized sometimes in a way to reconstruct Asad's method that is to make the methodology applicable to the subject matter. The main concepts used are 'ittiba' (adherence) legal practice, and Islamic habitus (Malakah). In order to investigate the total context, whom, contribute to the decisions' reasoning, the discussion include the opinions of the 'Ulama' toward commercial regulations into two apposite opinions disallowed then allowed. The legal education of the judges has direct impact to their reasoning, especially the shift of legal education from madrasah to university education. This shift made judges' Malakah suffered in understanding the law and their moral-orientation. In the sources of court decisions are not according to Hanbalism, that due to the clash of interests in the reality, which put pressure on the judges forum shopping from different schools of law to meet considered interest in the case. Meanwhile, the practice of sovereignty of the state particularly legislation has bad impact on the method of judges' reasoning. The solution to the sovereignty is the counter-power of people via networking to make a legal practice, and force the state follow it. The legal practice should be codified by the judges and 'Ulama', but not the state. The main contribution of the thesis is an analysis of Islamic law in the context from within its assumptions, which is very helpful to propose reasonable and applicable solution.